The nature of the beast - Penny, Louise (Penny, Louise. Three Pines mystery., 2015)
"Hardly a day goes by when nine year old Laurent Lepage doesn't cry wolf. From alien invasions, to walking trees, to winged beasts in the woods, to dinosaurs spotted in the village of Three Pines, his tales are so extraordinary no one can possibly believe him. Including Armand and Reine-Marie Gamache, who now live in the little Quebec village. But when the boy disappears, the villagers are faced with the possibility that one of his tall tales might have been true. And so begins a frantic search for the boy and the truth. What they uncover deep in the forest sets off a sequence of events that leads to murder, leads to an old crime, leads to an old betrayal. Leads right to the door of an old poet. And now it is now, writes Ruth Zardo. And the dark thing is here. A monster once visited Three Pines. And put down deep roots. And now, Ruth knows, it is back. Armand Gamache, the former head of homicide for the Sûreté du Québec, must face the possibility that, in not believing the boy, he himself played a terrible part in what happens next"--